GENDER DISTINCTIONS OF MICROALBUMINURIA AND ITS RELATION TO INTRARENAL HEMODYNAMIC AND LEPTIN LEVEL IN ARTERIAL HYPERTENSION - V. I. Podzolkov; A. E. Bragina; J. N. Rodionova (Рациональная фармакотерапия в кардиологии)
Aim. To assess an incidence of microalbuminuria (MAU) depending on gender and its relation to intrarenal hemodynamic, glomerular filtration rate (GFR), and leptin serum level in essential hypertension (HT). Material and methods. 149 patients (61 men and 88 women, aged 49.4±7.1 years, body mass index 32.2±3.8 kg/m2) with HT degree 2-3 were examined. Clinical characteristics in men and women were comparable. Ultrasonography of intrarenal vessels was performed in all patients. GFR was calculated by isotope nephroangioscintigraphy. Leptin serum level was determined\ by radioimmunoassay. MAU was detected by semiquantitative test. Results were processed with SPSS-11.0 software package. Results. MAU incidence was higher among female hypertensives in contrast to males: 40% vs 26% (p=0.056). Hypertensives with MAU of both genders demonstrated higher both resistance index (RI) and pulsatility index (PI). Gender differences of both RI and PI in patients with MAU were highly significant (p<0.001) at all levels of arterial visualization (renal, segmental and interlobar). Female hypertensives with MAU had lower GFR (79.1±13.2 ml/min/1.73m2) than those without MAU (89.3±17.2 ml/min/1.73m2). Male hypertensives with MAU had higher GFR than those without MAU: 126±32.5 vs 105.4±16.7 ml/min/1.73m2, respectively. Serum leptin level in females with MAU was higher than this in female patients without MAU: 103.5±38.7 vs 76.7±46.4 ng/ml (p=0.04), respectively. Leptin levels did not differ in males with or without MAU. In males MAU positively correlated with GFR (r=0.372, р=0.003), where-as in females – correlation was negative (r=-0.34, р=0.02). Besides, in females MAU correlated with serum leptin level (r=0.48, p=0.01) Conclusion. Female hypertensives with MAU demonstrate more stable elevation of RI and PI in contrast to hypertensive males with MAU. MAU level correlates with GFR in opposite ways: in males positively whereas in females — negatively.